Mapping Malaysia’s contribution to Gold Open Access: Growth patterns, disparities, and policy implications - Abidin, Azraai; Fairuzy, Norashikin; Abd. Rahman, Siti Salwa (Malaysian Journal of Library and Information Science, 2024)
This study examines the growth of Gold Open Access (OA) research output in Malaysia through a bibliometric analysis using Web of Science (WoS) data. Over the past decade, Malaysia has seen a significant increase in gold OA publications, ranking 27th globally, 10th in Asia, and first in Southeast Asia. The analysis reveals that Science & Technology and Health Sciences dominate the gold OA landscape, while Arts & Humanities and Social Sciences remain underrepresented. Malaysian researchers predominantly publish their gold OA articles in international journals, with Switzerland-based publishers being particularly prominent. A notable finding is the impact of government restrictions on using research funds for publications with three specific publishers - MDPI, Hindawi, and Frontiers. In 2023, MDPI experienced a 25.4 percent decline in publications by Malaysian researchers, reflecting a shift in publication patterns due to these restrictions. Despite the overall growth, the study highlights a mismatch between the quantity of gold OA publications and their citation impact, raising questions about the broader influence of Malaysian gold OA research. These findings underscore the need for strategies to manage and promote gold OA publishing effectively while addressing the challenges posed by policy restrictions. The insights offer valuable guidance for researchers and policymakers to optimize the benefits of gold OA publishing in Malaysia.